Does the type of pushing at delivery influence pelvic floor function at 2 months postpartum? A pragmatic randomized trial—The EOLE study. (9th November 2022) - Barasinski, Chloé; Debost‐Legrand, Anne; Savary, Denis; Bouchet, Pamela; Curinier, Sandra; Vendittelli, Françoise
Abstract: Introduction: Maternal pushing techniques during the second stage of labor may affect women's pelvic floor function. Our main objective was to assess the impact of the type of pushing used at delivery on the mother's medium‐term pelvic floor function. Material and methods: This is a secondary analysis of a randomized clinical trial (clinicaltrials.gov : NCT02474745) that took place in four French hospitals from 2015 through 2017 ( n = 250). Women in labor with a singleton fetus in cephalic presentation at term who had undergone standardized training in both of these types of pushing were randomized after cervical dilation ≥7 cm. The exclusion criteria were a previous cesarean, a cesarean delivery in this pregnancy or a fetal heart rate anomaly. In the intervention group, open‐glottis (OG) pushing was defined as a prolonged exhalation contracting the abdominal muscles to help move the fetus down the birth canal. Closed‐glottis (CG) pushing was defined as Valsalva pushing. The principal outcome was the stage of pelvic organ prolapse (POP) assessed by the Pelvic Organ Prolapse‐Quantification 2 months after delivery. A secondary outcome was incidence of urinary incontinence (UI). The results of our multivariable, modified intention‐to‐treat analysis are reported as crude relative risks (RRs) with their 95% confidence intervals. Results: Our analysis included 207 women. Mode of birth was similar in both groups. The two groups did not differ for stage II POP: 10 of 104 (9.4%) in the OG group compared with 7 of 98 (7.1%) in the CG group, for a RR 1.32, 95% confidence interval [CI] 0.52–3.33, and an adjusted RR of 1.22, 95% CI 0.42–3.6. Similarly, the incidence of UI did not differ: 26.7% in the OG group and 28.6% in the CG group (aRR 0.81, 95% CI 0.42–1.53). Subgroup analysis suggests that for secundiparous and multiparous women, OG pushing could have a protective effect on the occurrence of UI (RR 0.33, 95% CI 0.13–0.80). Conclusions: The type of directed pushing used at delivery did not impact the occurrence of pelvic organ prolapse 2 months after delivery. OG pushing may have a protective effect against UI among secundiparous and multiparous women. Abstract : The type of directed pushing, open‐glottis vs closed‐glottis, used by women with epidural analgesia during delivery does not affect their pelvic floor function 6‐8 weeks after delivery. The type of maternal pushing used during delivery should be chosen according to women's preferences, experience and ability.